Lactic Bacteria with Plant-Growth-Promoting Properties in Potato - Panetto, Lilian Dutra [UNESP]; Doria, Joyce; Santos, Carlos Henrique Barbosa [UNESP]; Frezarin, Edvan Teciano [UNESP]; Sales, Luziane Ramos [UNESP]; de Andrade, Luana Alves [UNESP]; Rigobelo, Everlon Cid [UNESP] (MDPI, 2023)
This study aimed to evaluate the abilities of three bacteria, Bacillus cereus, Succinovibrio dextrinosolvens, and Lactobacillus acidophilus, to fix nitrogen, solubilize phosphorus, and produce cellulosic and amylolytic enzymes. Then, these bacteria were evaluated in potato plants under field conditions. The bacterium B. cereus showed the ability to synthesize amylase, indole acetic acid (IAA) production of 9.08 μg mL−1, phosphorus solubilization of 14.93 mg P L−1, and nitrogen fixation of 0.7 mg of nitrogen L−1. S. dextrinosolvens showed the ability to synthesize siderophores and amylase, IAA production of 10.25 μg mL−1, phosphorus solubilization of 41.38 mg P L−1, and nitrogen fixation of 0.42 mg N L−1. L. acidophilus showed the ability to synthesize siderophores, IAA production of 7.25 μg mL−1, phosphorus solubilization of 5.58 mg P L−1, and nitrogen fixation of 0.5 mg N L−1. Some plant parameters were increased as shoot dry matter by B. cereus, and the mixture of bacteria increased shoot and root dry matter and increased phosphorus from the root. More studies are needed to deepen the understanding of the potential of these bacteria; however, B. cereus showed great potential to be used as a plant growth promoter in potato crops in the future.
Keywords: Bacillus cereus; chemical fertilizer; Lactobacillus acidophilus; potato